Tension Pistons: Amplifying Piston Force Using Fluid‐Induced Tension in Flexible Materials. (5th June 2019) - Li, Shuguang; Vogt, Daniel M.; Bartlett, Nicholas W.; Rus, Daniela; Wood, Robert J.
Abstract: Pistons are ubiquitous devices used for fluid‐mechanical energy conversion. However, despite this ubiquity and centuries of development, the forces and motions produced by conventional rigid pistons are limited by their design. The use of flexible materials and structures opens a door to the design of a piston with unconventional features. In this study, an architecture for pistons that utilizes a combination of flexible membrane materials and compressible rigid structures is proposed. In contrast to conventional pistons, the fluid‐pressure‐induced tension forces in the flexible membrane play a primary role in the system, rather than compressive forces on the internal surfaces of the piston. The compressive skeletal structures offer the opportunity for the production of tunable forces and motions in the "tension piston" system. The experimental results indicate that the tension piston concept is able to produce substantially greater force (more than three times), higher power, and higher energy efficiency (more than 40% improvement at low pressures) compared to a conventional piston, and these features enable myriad potential applications for the tension piston as a drop‐in replacement for existing pistons. Abstract : A new architecture for pistons, named "tension pistons, " is introduced. It utilizes a combination of flexible membrane and compressible rigid structures. In contrast to conventional pistons, the pressure‐induced tension forces in the membrane play a primary role in the tension pistons. The tension piston can outperform conventional pistons with greater force, higher power, and higher energy efficiency.